Environmental and Community Quality Improvement through Waste Bank Management and Utilization of Plastic Waste into High Value Ecobricks - Wicaksono, Naufal; Hasanah, Siti Muflihatul; Rosydah, Tyas; Hati, Dhipi Dara Laras; Fahrul, Mochamad Allan; Magfiroh, Illia Seldon (PT FORMOSA CENDEKIA GLOBAL, 2024)
Plastic waste is a major contributor to the accumulation of waste that endangers the environment. The solution to this problem is to manage waste banks and recycle plastic waste through ecobricks. The purpose of this community service activity is to increase community knowledge about waste bank management and ecobrick products as a first step to encourage environmental conservation, especially in Wonosari Village, Wonosari District, Bondowoso Regency. The community service method consisted of licensing, problem identification and solving, preparation of tools and materials, socialization of ecobricks, training on how to make ecobricks in the form of chairs and monitoring. The result of the community service is the increased awareness and concern of the community towards the problem of inorganic waste and being able to manage waste into valuable ecobrick products.